Regional Variation in Jespersen’s Cycle in Early Middle English - Walkden, George; Morrison, Donald Alasdair (Studia Anglica Posnaniensia, 2017)
In this paper we investigate the place of origin of the change from Jespersen’s Cycle stage II – bipartite ne + not – to stage III, not alone. We use the LAEME corpus to investigate the dialectal distribution in more detail, finding that the change must have begun in Northern and Eastern England. A strong effect of region and time period can be clearly observed, with certain linguistic factors also playing a role. We attribute the early onset of the change to contact with Scandinavian: North Germanic is known to have undergone Jespersen’s Cycle earlier in its history, and the geographical distribution of early English stage III fits neatly with the earlier boundaries of the Danelaw.